A genetically defined pontine nucleus essential for ingestion in mice - Selvee Sungeelee; Caroline Mailhes-Hamon; Zoubida Chettouh; Phillip Bokiniec; Annaliese Eymael; Simon McMullan; Clément Léna; Bowen Dempsey; Jean-François Brunet (Proceedings of the National Academy of Sciences, 2025)
The first phase of feeding consists in the procurement of solid foods from the environment by biting, and their preparation for swallowing by chewing. These actions require the precise coordination of tens of orofacial muscles for the jaw and tongue. The seat for this motor patterning is known to reside in the reticular formation, a complex and poorly mapped region of the hindbrain, but the neuron groups involved are still elusive. Here, we characterize a group of excitatory reticular interneurons located in the supratrigeminal area that express the homeodomain transcription factor Phox2b . This nucleus—Sup5 Phox2b —is premotor to both jaw-closing and jaw-opening motoneurons and receives direct input from cranial sensory afferents, motor cortex, and satiation related nuclei. Its activity differentially tracks lapping, biting, and chewing movements, suggesting its involvement in the elaboration of distinct orofacial motor patterns in vivo. Acute global activation or inhibition of Sup5 Phox2b by optogenetics interrupt volitional feeding sequences. Thus, Sup5 Phox2b is an obligatory subcortical node, topologically and genetically defined, in the neural circuits that control the oral phase of feeding in mice.